Export behaviour of micro firms in the Swedish computer and business service industries - Martin Falk; Eva Hagsten (Economics: The Open-Access, Open-Assessment E-Journal, 2015)
he export participation of SMEs in the Swedish computer and business service industries has increased rapidly over the last decade. Despite this, export participation rates-including those of micro enterprises-remained low at 13 per cent in computer services and 8 per cent in business services in 2010. Based on uniquely linked firm-level datasets with full coverage of micro enterprises, this study investigates the determinants of the export participation of Swedish SMEs in the computer and business service industries. Exports include both goods and services. Estimates based on the conditional fixed-effects logit model show a significantly positive relationship between initial labour productivity and the decision to export. One new and interesting finding is that the magnitude of the relationship between the probability to export and initial labour productivity is low when controlling for firm effects. Surprisingly, the impact of labour productivity on exporting in computer services does not differ between micro enterprises and other SMEs (10-249 employees). In business services, the relationship between export probability and labour productivity on the one hand and skill intensity on the other is significant for micro enterprises, but not for other SMEs (10-249 employees).
Keywords: F14; 330; exports; productivity; computer service industry; business services; human capital; conditional logit model